Learning outcomes: The long goodbye: Vocational qualifications in the 21st century. (January 2023) - Winch, Christopher
This article describes the origins of learning outcomes-based qualifications in England in the 1980s. It describes the design philosophy and evolution of National Vocational Qualifications (NVQs) which are contrasted with content-led frameworks and qualifications such as the English National Curriculum. The design flaws of the NVQ are noted and some policy implications of the NVQ experience are remarked on. It goes on to consider the adoption of learning outcomes approaches to qualifications in the European Union, first through the introduction of the European Qualification Framework (EQF) and then of European Skills, Competences, Qualifications and Occupations (ESCO). First, it is argued that the EQF serves as an umbrella for qualifications fundamentally incompatible with each other. Second, it is maintained that although ESCO has certain design features that liken it to the NVQ, it is also compatible with non-learning outcomes-based qualifications. Its assumptions about qualification design, based on task analysis, render it unsuitable as a template for the development of advanced vocational qualifications. The decline and fall of the NVQ and its replacement by standards-based qualification in England is described and some lessons that can be learned by policymakers are outlined. Learning outcomes-based qualifications are not fit for purpose.